2021
DOI: 10.3390/catal11091020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Galangin Derivatives and Cytotoxicity Evaluation of Their Metabolites

Abstract: Galangin (1), 3-O-methylgalangin (2), and galangin flavanone (3), the major bioactive flavonoids isolated from Alpinia officinarum, were biotransformed into one novel and four known metabolites (4–8) by application of the fungal strains Mucor hiemalis and Absidia coerulea as biocatalysts. Their structures were characterized by extensive spectroscopic analyses including one- and two-dimensional nuclear magnetic resonance spectroscopy and mass spectrometry. Compounds 1–7 were evaluated for their cytotoxic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The corresponding proton signals at δ H 4.50 (1H) and 3.69–3.19 (6H) were observed in the 1 H NMR spectrum. All of these data were consistent with previous reports on the d -glucose moiety [ 19 , 24 , 25 ], and the glucose was determined to be in a β-configuration by the large coupling constant (7.1 Hz) of the anomeric proton signal at δ H 4.50 (H-1‴). The significantly downfield-shifted aromatic proton signal at δ H 6.81 (H-2″) suggested the glucose moiety was attached to C-3″ through an ether linkage.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The corresponding proton signals at δ H 4.50 (1H) and 3.69–3.19 (6H) were observed in the 1 H NMR spectrum. All of these data were consistent with previous reports on the d -glucose moiety [ 19 , 24 , 25 ], and the glucose was determined to be in a β-configuration by the large coupling constant (7.1 Hz) of the anomeric proton signal at δ H 4.50 (H-1‴). The significantly downfield-shifted aromatic proton signal at δ H 6.81 (H-2″) suggested the glucose moiety was attached to C-3″ through an ether linkage.…”
Section: Resultssupporting
confidence: 91%
“…788.3983) in its HRFDMS spectrum, which was one glucose unit higher than that of 6 , indicating that two glucose units had been introduced into the molecule of 1 . The additional proton signals at δ H 4.64, 4.51 and 3.71–3.18 (12H), as well as the carbon signals at δ C 103.5, 101.5, 77.1, 76.9, 76.8, 75.8, 73.5, 73.4, 69.7, 69.6, 60.7, and 60.7 observed in the 1 H and 13 C NMR spectra of 7 , indicated the presence of two D-glucose residues [ 24 , 25 ]. The glucose units were identified as β-glucose by their large coupling constants (6.5 Hz and 6.6 Hz) of the anomeric proton signals δ H 4.64 and 4.51, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial transformation is a well-established green technique with high selectivity and efficiency to produce new and unique derivatives of bioactive substrates which are difficult to acquire by chemical synthesis under mild conditions [ 20 , 21 ]. It has been reported that microbial transformation of sesquiterpenes can result in derivatives with enhanced biological activities [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%